Development and Validation of Prediction Model for 02 and CO2 Concentration of Fresh Vegetables under Modified Atmosphere Packaging - . Sutrisno; Ferry R. Yuda Y.P (Jurnal Keteknikan Pertanian, 1999)
A mathematical model was developed to predic O2 and CO2 gaseous concentration for fresh vegetables under modified atmosphere packaging Mathematical models were developed by assump that the slides basin packing it permaeble and the bottom package is imperable.Verification of the model were done by using the experimental data of read chilli, carrot and tomato, the models were generally significant enough to predict the gaseous condition of inside package for fresh vegetables products under MAP.Key words : MAP, prediction models, shelf life, permabilitas, laju respirasi.